Islamic spirituality in medical imaging - Zainuddin, Zainul Ibrahim (2014)
The concept of spirituality has received much attention in healthcare. It is now accepted as part of patient-centered care. Related terminologies that include spiritual care and spiritual needs are also discussed alongside to spirituality. However, there is little to suggest about attention given to spirituality in Medical Imaging. This effectively gives the perception that Medical Imaging practitioners have little to contribute in patient- centered care. Furthermore, there exists no evidence concerning discussions directed to Islamic Spirituality in this sub-specialty of Medicine. This paper attempts to present the conceptualisation of Islamic Spirituality in a field that deals with the humanistic and technical dimensions. Concentrating on three areas in the field, the conceptualization relies on literatures mainly from Medicine and Nursing. It begins with establishing an understanding concerning spirituality and progressing to discussions pertaining to Islamic spirituality related to the practitioner, patient care and the practice. Attempts were also made to align those areas to primary and secondary sources of Islamic Spirituality. Based on published obstacles towards the application of spirituality in healthcare, possible solutions towards applying Islamic spirituality in Medical Imaging are proposed. It is hoped that the resultant harmonisation between spirituality and the practice will be able to trigger awareness and interests pertaining to the role of a Muslim practitioner in advocating and enhancing Islamic spirituality.